The efficacy and safety of sarilumab, fully human monoclonal antibodies against interleukin 6 receptor, in rheumatoid arthritis: new evidence - E. L. Nasonov; A. M. Lila (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is an immune-mediated inflammatory (autoimmune) rheumatic disease of unknown etiology, which is characterized  by chronic erosive arthritis (synovitis) and systemic damage of internal organs and leads to early disability and shorter life expectancy in patients. Much attention  is paid to studying the role of interleukin 6 (IL6) in the spectrum of proinflammatory cytokines involved in the pathogenesis of RA. The clinical introduction of anti-IL  receptor monoclonal  antibodies, such as tocilizumab and sarilumab, that inhibit the activity of this cytokine, is an important  step in the improvement  of RA treatment. The review considers the data from the main randomized controlled trials of the efficacy and safety of sarilumab in RA and discusses the prospects for using the drug to treat this disease.